Application of co-immobilized microbial biochar beads in hybrid biofilter towards effective treatment of chrome tanning wastewater. (August 2022) - Deepa, Arukula; Sonal, Sonalika; Mishra, Brijesh Kumar
Abstract: This paper aims to scrutinize the comparative performance of hybrid biofilter via column mode to boost the reduction rate of Cr (VI) and organic pollutants in various pre-treated tannery wastewater. The pre-treated water through aluminium formate, aluminium sulphate, and ferric chloride were passed through two divergent biofilter medium discretely with (i) immobilized sodium alginate microbial beads (Im/S.AM.B) and (ii) co-immobilized microbial biochar beads (Co-im/B.M.B). Biosorption efficiency of the hybrid biofilter was examined with respect to pH, initial adsorbate concentration, time, flow rate, breakthrough curve, and regeneration studies. The results exhibited that aluminium formate coagulant pre-treated wastewater when passed through Im/S.AM.B under optimized conditions, the reduction rate of Cr (VI), COD and sulphate was 92.5%, 89.5% and 75%, respectively, whereas Co-im/B.M.B surpassed it by 6.7%, 6.5% and 19% respectively, with a contact time of 90 min, flow rate 2 mL/min, depth 30 cm and pH 6. Further, the raw and treated sample of Co-im/B.M.B was studied for its morphology and surface chemistry via FE-SEM, EDX, FTIR and XRD analysis. The results revealed that Cr (VI) reduction is predominantly through precipitation, electrostatic attraction, and metal complexation. It was observed that electrostatic attraction of cationic charged biochar surface to Cr (VI) ions results in the reduction of Cr (VI) to Cr (III) and complexation between Cr (III). Further, the functional groups present on the microbial biomass (DPAML065) surface were also found responsible for Cr (VI) reduction. Thus, Co-im/B.M.B in hybrid biofilter presents an economical approach in reducing Cr (VI) from tannery wastewater. Graphical abstract: Unlabelled Image Highlights: Co-im/B.M.B showed 99.2% reduction of Cr(VI) with aluminium formate pre-treated tannery wastewater. Aluminium formate coagulant can increase biosorption competence of the hybrid biofilter with the addition of carbon source. Electrostatic attraction, redox reaction, and metal complexation are the predominant mechanisms during Cr(VI) reduction. Co-im/B.M.B can be regenerated with 0.4 M of NaOH and reused up to three cycles.